2014
DOI: 10.1002/iub.1313
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into RNA recognition properties of glyceraldehyde‐3‐phosphate dehydrogenase 3 from Saccharomyces cerevisiae

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH, EC: 1.2.1.12) is an essential enzyme in the glycolytic pathway. However, recent evidence demonstrates that GAPDH displays a range of new functions unrelated to its glycolytic function. GAPDH has long been known as a 3 0 AU-rich element-binding protein; however, its RNA recognition mechanism is still not well understood. Here, we present the first crystal structure of GAPDH3 from Saccharomyces cerevisiae and identify its RNAbinding specificity and propose an RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…29 The Sc GAPDH3 protein was shown to weakly bind AU-rich or Poly(A) RNA in vitro (K D of ~110-150 μM), but not Poly(U). 127 In contrast to mammalian GAPDH, Sc GAPDH3 showed higher affinity for shorter RNA with only one or two AUUUA motifs. In yeast cells, the GAPDH2 isoform was identified in a cross-link to an AU dinucleotide by mass spectrometry.…”
Section: Gapdh-rna Interactions Are Conserved In Other Speciesmentioning
confidence: 93%
See 1 more Smart Citation
“…29 The Sc GAPDH3 protein was shown to weakly bind AU-rich or Poly(A) RNA in vitro (K D of ~110-150 μM), but not Poly(U). 127 In contrast to mammalian GAPDH, Sc GAPDH3 showed higher affinity for shorter RNA with only one or two AUUUA motifs. In yeast cells, the GAPDH2 isoform was identified in a cross-link to an AU dinucleotide by mass spectrometry.…”
Section: Gapdh-rna Interactions Are Conserved In Other Speciesmentioning
confidence: 93%
“…Early studies showed that the Saccharomyces cerevisiae basic GAPDH isoform ( Sc GAPDH1) bound to poly(U) RNA and had a strong nucleic acid‐helix destabilizing effect . The Sc GAPDH3 protein was shown to weakly bind AU‐rich or Poly(A) RNA in vitro ( K D of ~110–150 μM), but not Poly(U) . In contrast to mammalian GAPDH, Sc GAPDH3 showed higher affinity for shorter RNA with only one or two AUUUA motifs.…”
Section: Gapdh–rna Interactions Are Conserved In Other Speciesmentioning
confidence: 99%
“…TDH3 encodes an isozyme of the yeast glyceraldehyde-3-phosphate dehydrogenase (GAPDH) involved in glycolysis and gluconeogenesis ( McAlister and Holland, 1985 ) as well as transcriptional silencing ( Ringel et al, 2013 ), RNA-binding ( Shen et al, 2014 ) and possibly antimicrobial defense ( Branco et al, 2014 ). Variation in this gene’s promoter affecting expression noise has previously been shown to be a target of selection in natural populations ( Metzger et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), an important enzyme in the carbohydrate metabolism, is responsible for the oxidative phosphorylation of glyceraldehyde-3-phosphate into 1-3-diphosphoglycerate in the presence of nicotinamide adenine dinucleotide (NAD + ). Despite its importance for glycolysis and gluconeogenesis, studies have presented other roles of GAPDH such as DNA replication and repair, membrane fusion and transport and tRNA export, [42].…”
Section: Resultsmentioning
confidence: 99%